Modelling Online Purchase Behavior from Consumer Decision Model Perspective - Ni Luh Putu Indiani; Ni Made Purnami (APMBA (Asia Pacific Management and Business Application), 2021)
Despite the significant growth of internet users in Indonesia, the use of the internet for online shopping is still quite low, which hinders the potential for e-commerce growth in Indonesia. This fact raises interest in analyzing factors that influence online shopping intention among Indonesians. Based on consumer decision model, this study developed an online purchase decision model using an integrative approach that includes factors of marketing stimuli, environmental influence, and consumer concern altogether. This integrative model is aimed to get a more comprehensive picture of online purchase behavior, as previous studies analyzed this object using only one or two of these three factors. A survey was conducted to collect data using questionnaire as the instrument. Respondents were consumers who have bought retail products online. Data were analyzed using Partial Least Square. The results showed that website quality, eWOM, and perceived benefit significantly influence online purchase intention through the mediation of trust. Practical implications are discussed further.